Comparative study of attitudes to religious groups in New Zealand reveals Muslim-specific prejudice. (2nd July 2020) - Greaves, Lara M.; Rasheed, Aarif; D'Souza, Stephanie; Shackleton, Nichola; Oldfield, Luke D.; Sibley, Chris G.; Milne, Barry; Bulbulia, Joseph
ABSTRACT: The March 15th terrorist attack started a national dialogue about prejudice in New Zealand. Previous research has investigated attitudes towards Muslims in comparison to ethnic minorities. However, presently, there are no nationally representative studies in New Zealand systematically comparing attitudes to Muslims with attitudes to other religious groups. Here, we present evidence from the New Zealand edition of the International Social Survey Programme module on religion, a national postal survey ( N  = 1335) collected between September 2018 and February 2019. We assess perceived threat and negativity towards Christians, Muslims, Hindus, Buddhists, Jews, and Atheists. We find substantially greater perceived threat and negativity towards Muslims compared with other groups. In particular, older people, New Zealand Europeans, men, and those with more right-wing attitudes report greater threat and negativity towards Muslims. In line with previous studies, higher religious identification and higher education predict greater acceptance. Taken collectively, these results reveal that the Muslim Acceptance Gap in this country is substantial, and greater challenges for acceptance are evident among lower-educated, right-wing, older, secular, and male populations. The magnitude of this gap reveals a substantial challenge to the future of New Zealand where religious and secular people can live without evoking prejudice.